Professional Learning Community (PLC) w Singapurze: możliwości i ograniczenia w kształtowaniu wysokiej jakości edukacji - Nowosad, Inetta (Rocznik Pedagogiczny, 2020)
The aim of this article is to recognise the Professional Learning Communities (PLC) model adopted in 2009 in Singapore as a national mode. The explicit use of the term of PLC together with related terms makes it possible to understand an educational policy which is focused on the implementation of concepts developed in a different, foreign context. The orientation adopted in Singapore identifies PLC not only as reinforcing incentives for teachers and their professionalism, but more broadly, as reinforcing the already high-quality education. The arguments and evidence presented in this article are mainly based on literature and research review, as well as on analyses of source documents.